The efficacy of non-pharmacological interventions for treating constipation symptoms in lung cancer patients: a systematic review and network meta-analysis - Cai, Mian; Yin, Jie; Fang, Xiwei; Li, Yanjing; Hu, Liuxin; Xu, Yiyong (Frontiers in Oncology, 2025)
ObjectiveThis study aims to comprehensively evaluate the efficacy of different non-pharmacological interventions in treating constipation symptoms in lung cancer patients through a network meta-analysis, providing evidence-based support for personalized treatment decisions in clinical practice.MethodsWe retrieved randomized controlled trials (RCTs) from well-known databases and compared the efficacy of non-pharmacological interventions with traditional treatments or placebos in improving constipation symptoms in lung cancer patients. The search was conducted through January 2025. Two researchers independently screened the literature, extracted data, and assessed the quality of the studies using the Cochrane risk of bias tool. Traditional meta-analysis was performed using Stata 16.0 software. Network meta-analysis (NMA) was conducted using RStudio software to integrate the data and create a network diagram to display the comparisons between non-pharmacological interventions. The credibility of the evidence was assessed using the Confidence in Network Meta-Analysis (CINeMA) tool.ResultsA total of 33 studies involving 3,471 participants were included in this study. The traditional meta-analysis revealed that non-pharmacological interventions effectively reduced the incidence of constipation and improved constipation symptom management in lung cancer patients during treatment. Additionally, these interventions positively impacted the time to first bowel movement and reduced negative emotions (such as anxiety) in hospitalized lung cancer patients with constipation. The network meta-analysis (31 studies, 3,287 participants) indicated that acupoint stimulation was the most effective non-pharmacological intervention for reducing constipation incidence in lung cancer patients during treatment. The combined use of two types of acupoint patches showed optimal efficacy in improving constipation symptoms. However, for overall therapeutic effectiveness, the combination of acupoint patch therapy and acupoint massage most effectively reduced constipation incidence and improved overall constipation symptom management in lung cancer patients during treatment.ConclusionThe combination of acupoint patch therapy and acupoint massage is recommended as the preferred clinical intervention for treating constipation symptoms in lung cancer patients.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42025631567.